MULTIDIMENSIONAL ANALYSIS ON WORK-FROM-HOME IN COVID-19 PANDEMIC - Afzal, Seema; binti Abdul Ghani Azmi , Ilhaamie (Online Journal of Islamic Management and Finance (OJIMF), 2022)
Contemporary worldwide disaster COVID-19 encountered by people seemed to be widely spread like a fire in the jungle. This surge impacted the lives of many, even caused fatalities. Staying at home and not to go outside is one of the hot topics of the moment. The population around the world found a major lapse when it was noticed that the epidemic COVID-19 is infecting both Muslims and non-Muslims. Meanwhile, due to this worldwide disaster, countries facing the issue altered their work status into work from home. This study was conducted by collecting the readily available secondary data from previous studies and recently published articles on the several worldwide pandemics. This study discussed the effects of COVID-19 on the population especially, organizations with the practice of work from home. It also discussed the effectiveness of social distancing to avoid the spread of this virus. Moreover, this study discussed the benefits of work from home along with enlightening the Islamic perspectives to strengthen the study.